2002
DOI: 10.3758/cabn.2.3.187
|View full text |Cite
|
Sign up to set email alerts
|

The impact of synaptic depression following brain damage: A connectionist account of "access/refractory" and "degraded-store" semantic impairments

Abstract: Neuropsychological studies of patients with acquired semantic impairments have yielded two distinct and contrasting patterns of performance in a spoken-word/picture-matching task (Warrington & Cipolotti, 1996). Patients labeled access/refractory are strongly influenced by presentation rate, semantic relatedness of distractors, and repetition, yet they seem relatively unaffected by lexical frequency. Degraded-store patients, on the other hand, are strongly affected by lexical frequency but are less affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 124 publications
(206 reference statements)
3
73
1
Order By: Relevance
“…Models of lexical access in language production assume that semantic interference in naming arises when accessing lexical representations from meanings (Damian et al, 2001;Howard et al, 2006;Levelt et al, 1999;Oppenheim et al, 2010;Roelofs, 1992, whereas theories of semantic interference in language comprehension assume that the effect arises when accessing semantic representations of a given word (Campanella & Shallice, 2011;Forde & Humphreys, 1997Gotts & Plaut, 2002;Warrington & Cipolotti, 1996;Warrington & McCarthy, 1983, 1987. Our findings demonstrating separate neural loci of semantic interference in language production and comprehension provide support for this hypothesis.…”
Section: Locus Of Semantic Interferencesupporting
confidence: 67%
See 2 more Smart Citations
“…Models of lexical access in language production assume that semantic interference in naming arises when accessing lexical representations from meanings (Damian et al, 2001;Howard et al, 2006;Levelt et al, 1999;Oppenheim et al, 2010;Roelofs, 1992, whereas theories of semantic interference in language comprehension assume that the effect arises when accessing semantic representations of a given word (Campanella & Shallice, 2011;Forde & Humphreys, 1997Gotts & Plaut, 2002;Warrington & Cipolotti, 1996;Warrington & McCarthy, 1983, 1987. Our findings demonstrating separate neural loci of semantic interference in language production and comprehension provide support for this hypothesis.…”
Section: Locus Of Semantic Interferencesupporting
confidence: 67%
“…We tested subjects with left hemisphere stroke using structural magnetic resonance and diffusion tensor imaging to investigate first, whether semantic interference in language production and comprehension arises at different brain loci as suggested by cognitive models (e.g., Belke, 2013;Damian et al, 2001;Howard et al, 2006;Levelt et al, 1999;Oppenheim et al, 2010;Roelofs, 1992Gotts & Plaut, 2002;Warrington & Cipolotti, 1996) and second, whether interference in both modalities share a common neural mechanism that acts to resolve competition from co-activated same category representations (Badre, Poldrack, ParĂ©-Blagoev, Insler, & Wagner, 2005;Badre & Wagner, 2007;Jefferies & Lambon Ralph, 2006;Novick, Trueswell, &Thompson-Schill, 2005cf. Biegler et al, 2008;Hamilton & Martin, 2005;McCarthy & Kartsounis, 2000;Schnur et al, 2006Schnur et al, , 2009Wilshire & …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, using an implemented model of semantic processing, Gotts and Plaut (2002) demonstrated that refractory effects can result from neuromodulatory deficits, which generate increased synaptic depression, thus reducing the efficiency with which new stimuli can override current processing during the refractory period. Although this theory does not explicitly consider the issue of modality, if extended to an amodal semantic system, it would predict refractory effects for both verbal and nonverbal tasks, with the effect for both arising from the same general neuromodulatory deficit.…”
Section: Verbal-only Versus Multimodal Refractory Effectsmentioning
confidence: 99%
“…Also, as mentioned earlier, Laing and Chow (2002) simulated binocular rivalry using synaptic depression mechanisms. Most recently, damage to synaptic depression processes has been proposed as the mechanism underlying an acquired neurophsychological deficit in semantic processing referred to as "access/refractory" (Gotts & Plaut, 2002).…”
Section: Synaptic Depressionmentioning
confidence: 99%